Dicrostonyx hudsonius - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Dicrostonyx hudsonius (Pallas, 1778). Nova Spec. Quad. Glir. Ord., p. 208. TYPE LOCALITY: Canada, Labrador. DISTRIBUTION: Labrador and N Quebec, Canada. COMMENTS: Unbanded karyotype resembles that of D. richardsoni (see Kröhne, 1982). Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 510, DOI: 10.5281/zenodo.7353098